CURRENT PROBLEMS AND PROSPECTS OF STATE ENVIRONMENTAL POLICY IN UKRAINE - V.V., Hlukha (Pressing Problems of Public Administration, 2016)
Reviewed and researched current issues and prospects of the state ecological policy of Ukraine and de ned the priority directions of long-term strategy of solving environmental problems in Ukraine at the national, regional, local and object levels.